Peningkatan Motivasi Belajar Siswa dengan Mengoptimalkan Penerapan Model Discovery Learning dalam Mata Pelajaran PAK dan Budi Pekerti - Alvemin Alvemin (Universitas Tadulako, 2021)
The purpose of this study was to determine the effectiveness of the application of the Discovery Learning model in increasing student motivation in Christian Religious Education (PAK) and Budi Pekerti subjects in class VII SMPN 9 Palu. This type of research is classroom action research (CAR). This research consists of two cycles. Each cycle goes through the stages of planning, implementing, observing and reflecting. Data collection techniques in this research using the observation method. The instrument in this research is in the form of an observation sheet. Based on the results of the study, the score in the first cycle of teacher observations was 3.86, which increased in the second cycle to 4.36. The results of student observations in the first cycle of 3.60 increased in the second cycle to 4.24. The presentation of students in the first cycle was 3.86 and increased in the second cycle to 4.2. These results indicate that the application of the discovery learning model can increase students' learning motivation in PAK and morals subjects in class VII SMPN 9 Palu.